2020
DOI: 10.12662/2317-3076jhbs.v8i1.2979.p1-6.2020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of chloramphenicol-florfenicol resistance (cfr) genes among linezolid resistant MRSA isolates in Sokoto State, Nigeria

Abstract: Objective: we investigated previous literatures for documentation of the trend in Sokoto, Nigeria and found none. We deemed it fit to determine the frequency of linezolid resistance mediated by cfr gene among MRSA isolates from Sokoto State-owned hospitals. Methods: Bacterial species identification was carried out with Microgen™ Staph-ID System kit (Microgen, Surrey, UK). Disc agar diffusion method (Modified Kirby-Bauer's) following Clinical and Laboratory Standards Institute (CLSI 2018) guidelines was used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…It has been reported that in Nigeria isolated 81 samples of S. aureus from the samples sent to the laboratory, and in the disk diffusion agar method, using oxacillin antibiogram, it has been obtained 46.9% of methicillin-resistant S. aureus. Also, in the PCR technique, the cfr gene (resistance to linezolid) was reported by 17.4% [35]. This study is consistent in terms of technique, antibiogram method and linezolid antibiotic resistance.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that in Nigeria isolated 81 samples of S. aureus from the samples sent to the laboratory, and in the disk diffusion agar method, using oxacillin antibiogram, it has been obtained 46.9% of methicillin-resistant S. aureus. Also, in the PCR technique, the cfr gene (resistance to linezolid) was reported by 17.4% [35]. This study is consistent in terms of technique, antibiogram method and linezolid antibiotic resistance.…”
Section: Discussionsupporting
confidence: 82%